The relationship between training and development approaches and employee capabilities in Sabah state ministries - Mahra Salleh (2010)
The main purpose of this study was to determine the relationship between training and development approaches and employee capabilities. This study was conducted in ten ( 10) Sabah state ministries namely Ministry of Finance, Ministry of Rural Development, Ministry of Tourism, Culture and Environment, Ministry of Community Development and Consumer Affairs, Ministry of Infrastructure Development, Ministry of Agriculture and Food Industry, Ministry of Local Government and Housing, Ministry of Industrial Development, Ministry of Youth and Sports, Ministry of Resource Development and Information Technology. A total of 219 employees were selected as the sample of the study by using self-administered questionnaire survey forms and convenience purposive sampling, and the hypotheses analyzed using the Statistical Package for Social Science (SPSS). This quantitative study employed a survey methodology to examine the relationship between the independent variables (selected coaching, mentoring and management development) and the dependent variable (employee capabilities). Besides, this study also aim at determination of the effect of three moderating variables (age, length of service, and education level) on the relationship between training and development approaches and employee capabilities. The findings of the study show that there is no significant relationship between coaching and mentoring and employee capabilities. However, there is a significant relationship between management development and employee capabilities. Additionally, the finding also reveals that two (2) moderating variables (age and length of service of employee) do not significantly moderate the relationship between training and development approaches and employee capabilities. However, education level of employee does significantly moderate the relationship between training and development approaches and employee capabilities.